V.l.n.r. voor: Pronk, Van Thijn. Achter Ter Beek, rechts van hem: Poppe. Nog vaag te zien, uiterst rechts: Voogd - Naeff, Nico
V.l.n.r. voor: Pronk, Van Thijn. Achter Ter Beek, rechts van hem: Poppe. Nog vaag te zien, uiterst rechts: Voogd.